PENGUKURAN SIKAP WISATAWAN DOMESTIK TERHADAP DESTINASI-DESTINASI WISATA INDONESIA DENGAN MENGGUNAKAN IDEAL POINT MODEL - Yusendra, Muhamad Ariza Eka (Jurnal Manajemen Magister Darmajaya, 2016)
This study objectives is to determine the attitude of domestic tourists from several tourism destinations in Indonesia, such as Bali, Yogyakarta, DKI Jakarta, Bandung, Surabaya, Semarang, Solo, Lampung, and Palembang based on attitude forming attributes of domestic tourists toward the tourism destinations using Ideal Point model. Ideal Point model is chosen in this measurement because this model able to provide information about consumer desires (ideal) and consumer real feelings according to the importance of attribute. This research used the data of 400 respondents of domestic tourists with the survey method. The result of attitude analysis using Ideal Point model is that Bali has very good attitude interpretation from tourists prepective and is in the first rank. Then, it is followed respectively by Yogyakarta (very good), Bandung (good), DKI Jakarta (good), Surabaya (good), Semarang (good), Palembang (ordinary), and Lampung(ordinary).Â Keywords: Domestic tourists attitude, ideal point model, tourism destination